An academic literacies argument for decentralizing EAP provision. (28th March 2016) - Murray, Neil
Abstract: English-medium universities have generally adopted centralized models of in-sessional English language provision, where expertise resides and is often delivered within language development units or as part of larger cognate departments, typically TESOL or Applied Linguistics departments. This arrangement might be seen as reflecting a one-size-fits-all study skills perspective on EAP, one that treats the development of student writing, in particular, as mastery of a set of skills that are generalizable across different disciplines. With the emergence of the 'academic literacies' perspective, this emphasis has shifted somewhat towards an approach that gives greater recognition to the variation which exists between the writing practices of different academic disciplines. This shift provides support for a move away from a centralized model of English language provision to a decentralized approach that brings with it a number of distinct benefits outlined in this article.